2020
DOI: 10.1038/s41396-020-00784-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial dynamics in the apple flower microbiome in the presence of the phytopathogen Erwinia amylovora

Abstract: Plant microbiomes have important roles in plant health and productivity. However, despite flowers being directly linked to reproductive outcomes, little is known about the microbiomes of flowers and their potential interaction with pathogen infection. Here, we investigated the temporal spatial dynamics of the apple stigma microbiome when challenged with a phytopathogen Erwinia amylovora, the causal agent of fire blight disease. We profiled the microbiome from the stigmas of individual flowers, greatly increasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 53 publications
5
43
0
Order By: Relevance
“…For example, the abiotic environment has been reported to strongly drive the composition of the plant microbiome, including soil [ 1 , 2 , 3 ], atmosphere [ 4 ], geography [ 5 , 6 ], and many others. In addition, the plant microbiome is under the influence of many biotic factors, some of them exogenous like herbivory [ 1 , 7 ] or plant diseases [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], some others are instead driven by the plant itself. Indeed, previous studies reported variation in the structure of plant microbiomes according to compartment (e.g., root, leaf, fruit, flower) [ 18 ], but also within the same compartment, for example between different parts of flowers and fruits, or between internal and external tissues [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the abiotic environment has been reported to strongly drive the composition of the plant microbiome, including soil [ 1 , 2 , 3 ], atmosphere [ 4 ], geography [ 5 , 6 ], and many others. In addition, the plant microbiome is under the influence of many biotic factors, some of them exogenous like herbivory [ 1 , 7 ] or plant diseases [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], some others are instead driven by the plant itself. Indeed, previous studies reported variation in the structure of plant microbiomes according to compartment (e.g., root, leaf, fruit, flower) [ 18 ], but also within the same compartment, for example between different parts of flowers and fruits, or between internal and external tissues [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1079, were isolated from apple flower stigma samples collected on the apple cultivar ‘Early Macoun’ ( Malus x domestica NY75414-1) planted at Lockwood Farm in Hamden, CT (41.406°N, 72.906°W) ( 1 ). Our previous data showed that Enterobacteriaceae and Pseudomonadaceae are the two predominant families of bacteria on apple stigma ( 2 , 3 ). Within the Enterobacteriaceae , the genera Pantoea and Erwinia were predominant, and within the Pseudomonadaceae , Pseudomonas was the principal genus ( 3 ).…”
Section: Announcementmentioning
confidence: 99%
“…Our previous data showed that Enterobacteriaceae and Pseudomonadaceae are the two predominant families of bacteria on apple stigma ( 2 , 3 ). Within the Enterobacteriaceae , the genera Pantoea and Erwinia were predominant, and within the Pseudomonadaceae , Pseudomonas was the principal genus ( 3 ). The genus Curtobacterium , belonging to the phylum Actinobacteria , was much less abundant in the microbiome and was investigated as a representative of the apple stigma “rare biosphere” ( 3 ).…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…The apple microbiome depends on many factors such as genotype, management practices, and more [1,[47][48][49][50][51]. A recent study indicated that the abundance and distribution of bacterial phyla in the "Royal Gala" apple fruit were consistent in most examined countries [1].…”
Section: Introductionmentioning
confidence: 99%